COLLABORATIVE ONLINE INTERNATIONAL LEARNING: SUGGESTIONS FOR UKRAINIAN MEDICAL EDUCATION AND INTERDISCIPLINARY COOPERATION - Yu.V. Lysanets; J. Ward; C. Zhang; T. Downing; O.M. Bieliaieva (Проблеми екології та медицини)
This paper examines the experience of implementing Collaborative Online International Learning (COIL) projects at Coventry University and explores their potential application in the context of Ukrainian higher medical education. The aim of this paper is to demonstrate the feasibility of applying Coventry University's experience in organizing and implementing COIL exchanges in the academic setting of medical and ecological education in Ukraine, thereby fostering enriching opportunities for students and staff to collaborate at the intersection of healthcare, sustainability, business, and law. Materials and methods. The authors outlined the benefits of COIL initiatives between partners, as well as possible challenges in their implementation relying on the corpus of research papers published within the last 5 years available online in PubMed, Google Scholar and other databases, applying the methods of analysis and synthesis, systematization, generalization, comparative and contrastive methods. Results. Given the current conditions of the Russian invasion and martial law in Ukraine, COIL seems to be particularly relevant, providing a vital avenue for global collaboration in education when physical travel abroad may be difficult or impossible. The emphasis on cultural immersion, global perspectives, and the adaptability of the projects make COIL a promising direction for enriching both students and staff within the Ukrainian higher education framework. Highlighting the transformative potential of COIL, the paper proposes potential topics for interdisciplinary COIL projects between healthcare, ecology, business & law professionals. Conclusions. In the context of Ukrainian higher education, the paper suggests that adopting COIL exchanges could enhance collaboration between institutions, empowering students and providing flexible tools for achieving educational objectives. COIL exchanges offer a pathway to enhance educational outcomes while nurturing vital skills and perspectives essential for students and staff to thrive in an increasingly interconnected world.